Monitoring of fibrinolytic system activity with plasminogen, D-dimers and FDP in primary total knee arthroplasty (TKA) after topical, intravenous or combined administration of tranexamic acid - Jiri Lostak; Jiri Gallo; Ludek Slavik; Jana Zapletalova; Lubos Balaz (Biomedical Papers, 2020)
Aim: We assessed various ways of tranexamic acid (TXA) administration on the fibrinolytic system. Blood loss, transfusions, drainage and haematoma were secondary outcomes. Methods: In this prospective study, we examined 100 patients undergoing primary total knee arthroplasty (TKA) between June and November 2018. Patients were randomly assigned to 4 groups according to the following TXA regimens: 1) loading dose 15 mg TXA/kg single intravenous administration applied at initiation of anesthesia (IV1); 2) loading dose 15 mg TXA/kg + additional dose 15 mg TXA/kg 6 h after the first application of TXA (IV2); 3) IV1 regime in combination with a local wash of 2 g of TXA in 50 mL of saline (COMB); 4) topical administration of 2 g of TXA in 50 mL of saline (TOP). Results: Systemic fibrinolysis interference was insignificant in all of the regimens; we did not detect significant differences between IV1, IV2 and COMB in the monitored parameters within the elapsed time after the TKA; IV regimes had the lowest total drainage blood loss; the lowest blood loss was associated with the IV1 and IV2 regimens (IV1, IV2 < COMB < TOP); the lowest incidence of haematomas was in patients treated with TXA topically (i.e., in COMB + TOP). Conclusion: The largest antifibrinolytic effect was associated with intravenous administration of TXA. In terms of blood loss, intravenously administered TXA can interfere with the processes associated with the formation of the fibrin plug more efficiently than the simple washing of wound surfaces with TXA.